2020
DOI: 10.1029/2019jd031926
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation Probability and Its Future Changes From a Global Cloud‐Resolving Model and CMIP6 Simulations

Abstract: This study investigates precipitation probability and its future changes using simulations from the Non‐hydrostatic Icosahedral Atmospheric Model (NICAM), a global cloud‐resolving model, and Coupled Model Intercomparison Project Phase 6 (CMIP6) models. For the precipitation probability comparison between models and Tropical Rainfall Measuring Mission (TRMM) during 1998–2008, the difference is greatly reduced by regridding to a common coarser resolution, but the difference signs largely remain. Both NICAM and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 85 publications
2
39
0
Order By: Relevance
“…NICAM can well simulate the spatiotemporal variations of convective clouds over Tibetan Plateau (Sato et al., 2007, 2008), and diurnal precipitation cycle and nocturnal precipitation over southern slope of the Tibetan Plateau (Dirmeyer et al., 2011). It has been used to investigate the response of global precipitation and monsoon precipitation to climate change in the future (e.g., Na et al., 2020; Takahashi et al., 2020). Herein, we focus on the Tibetan Plateau by using the NICAM AMIP‐type simulation for the historical period from 1979 to 2008 and future period from 2075 to 2104 under A1B scenario.…”
Section: Methodsmentioning
confidence: 99%
“…NICAM can well simulate the spatiotemporal variations of convective clouds over Tibetan Plateau (Sato et al., 2007, 2008), and diurnal precipitation cycle and nocturnal precipitation over southern slope of the Tibetan Plateau (Dirmeyer et al., 2011). It has been used to investigate the response of global precipitation and monsoon precipitation to climate change in the future (e.g., Na et al., 2020; Takahashi et al., 2020). Herein, we focus on the Tibetan Plateau by using the NICAM AMIP‐type simulation for the historical period from 1979 to 2008 and future period from 2075 to 2104 under A1B scenario.…”
Section: Methodsmentioning
confidence: 99%
“…A modified version of the Mellor-Yamada level 2 scheme (Nakanishi and Niino, 2006;Noda et al, 2010) is used to simulate the planetary boundary layer. The radiation scheme, mstrnX (Sekiguchi and Nakajima, 2008), is a broadband model with 29 radiation bands as used here.…”
Section: Overviewmentioning
confidence: 99%
“…In addition, the coupling provides model developers with a better understanding of the origins of model biases (Hashino et al, 2016). The mstrnX scheme requires a database of singlescattering properties of hydrometeors (RADPARA), including parameters such as the volume extinction coefficient, absorption coefficient, asymmetry factor, and second moment of phase function (Nakajima et al, 2000). In NICAM16-S we used the RADPARA database revised by .…”
Section: Coupling Between Cloud Microphysics and Radiative Transfermentioning
confidence: 99%
“…research and in evaluation of the climate model simulations (e.g., Demory et al, 2013;Giorgi et al, 2014;Su et al, 2015;Wehner et al, 2010). However, the uncertainty in derived precipitation probability varies from different satellite data sets (e.g., Gebremicael et al, 2019;Giorgi et al, 2014;Liang et al, 2019;Na et al, 2020;Sun et al, 2018;Sylla et al, 2013;Xu et al, 2014). It is useful to use multiple analysis datasets to provide insight to the observational uncertainties.…”
Section: Accepted Articlementioning
confidence: 99%
“…Compared with TRMM, the GPCP has a significantly smaller variance. This is because GPCP significantly underestimates the heavy precipitation (e.g., Na et al, 2020). Na et al (2020) suggested that it should be cautious to use the GPCP for the model evaluation, especially for the heavy precipitation (see their Figure 2).…”
Section: Accepted Articlementioning
confidence: 99%